Exploring immersive learning technology as learning tools in experiential learning for architecture design education - Annisa Ummihusna; Mohd Zairul (Emerald Publishing, 2022)
Purpose: Formal architecture curriculum necessitates students to observe their architectural experience and environment, which cannot be comprehended entirely in a classroom alone. However, complications in handling site visits and the Covid-19 pandemic can affect their overall learning experience. This study seeks to uncover (1) how a learning tool can be designed to actively enrich novice designers' personal spatial understanding and (2) how will the experiential learning (EL) with immersive learning technology (ILT) replace the actual concrete experience (CE) in enriching the novice designers' personal spatial experience during the architecture design process. Design/methodology/approach: The current research focuses on novice designers (first-year architecture students) who seem to lack personal spatial experience. Findings from a personal spatial experience survey (PSES) conducted in the earlier stage of the research established that each learner had had a different level of spatial experience, which affected their approach in the design process. A learning tool called Architectural Spatial Experience Simulation (ASES) was designed, developed, implemented and evaluated with an experiential learning model (ELM) framework. Findings: The findings suggest that the use of ASES in the ELM significantly increased the learners' spatial experience. However, the simulation and framework demonstrated a different effect on the participants' spatial experience, particularly on learners with minimal spatial experience. Originality/value: This study benefits the architecture learning process by providing a tool and a framework to remedy the emerging issue concerning novice designers. The finding contributes to the body of knowledge by expanding the application of EL theory in architecture education.